Direct probing of anode arc root dynamics and voltage instability in a dc non-transferred arc plasma jet. (13th October 2015) - Ghorui, S; Tiwari, N; Meher, K C; Jan, A; Bhat, A; Sahasrabudhe, S N
Abstract: The transient dynamics of the anode arc root in a dc non-transferred arc plasma torch is captured through fast photography and directly correlated with the associated voltage instability for the first time. The coexistence of multiple arc roots, the transition to a single arc root, root formation and extinction are investigated for the steady, takeover and re-strike modes of the arc. Contrary to the usual concept, the emerging plasma jet of a dc non-transferred arc plasma torch is found to carry current. An unusually long self-propelled arc plasma jet, a consequence of the phenomenon, is demonstrated.